Discovery of N-(2-Amino-4-Fluorophenyl)-4-[bis-(2-Chloroethyl)-Amino]-Benzamide as a Potent HDAC3 Inhibitor - Chen, Yiming; Feng, Jinhong; Hu, Yajie; Wang, Xuejian; Song, Weiguo; Zhang, Lei (Frontiers in Oncology, 2020)
In discovery of HDAC inhibitors with improved activity and selectivity, fluorine substitution was performed on our previously derived lead compound. The synthesized molecules N-(2-amino-4-fluorophenyl)-4-[bis-(2-chloroethyl)-amino]-benzamide (FNA) exhibited class I (HDAC1, 2, and 3) selectivity in the in vitro enzymatic assay and especially potent against HDAC3 activity (IC50: 95.48 nM). The results of in vitro antiproliferative assay indicated that FNA exhibited solid tumor cell inhibitory activities with IC50 value of 1.30 μM against HepG2 cells compared with SAHA (17.25 μM). Moreover, the in vivo xenograft model study revealed that FNA could inhibit tumor growth with tumor growth inhibition (TGI) of 48.89% compared with SAHA (TGI of 48.13%). Further HepG2 cell–based apoptosis and cell cycle studies showed that promotion of apoptosis and G2/M phase arrest make contributions to the antitumor activity of FNA. In addition, drug combination results showed that 0.5 μM of FNA could improve the anticancer activity of taxol and camptothecin. The present studies revealed the potential of FNA utilized as a high potent lead compound for further discovery of isoform selective HDAC inhibitors.